The effects of dietary mineral regimen on starter pig growth performance and blood and immune parameters - Smith, J.W.II; Arthington, J.D.; Blecha, Frank; Richert, B.T.; Owen, K.Q.; Bergstrom, J.R.; Nessmith, W.B. Jr.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two hundred sixty-six weanling pigs (initially 12.461b and 21 d of age) were used in a 34-<1 growth assay to evaluate the effects of various mineral supplementation regimens on starter pig growth, immune status, blood parameters, and liver mineral status.. Pigs were fed either a control diet, 3,000 ppm zinc (Zn) in phase I and 2,000 ppm Zn in phase II and III, 250 ppm copper during the entire trial, or a combination of these three diets. These results support our current recommendations of adding zinc oxide in diets of pigs weighing up to 25 lb and copper sulfate in diets fed to pigs from 25 to 50 lb.
Keywords: Swine; Starter; Zinc; Copper; Performance; Pigs